The Leadership Role of the Principal in Improving the Competitiveness of Madrasah Tsanawiyah Nahdlatul Muslimat Surakarta - Khasanah, Munib Amaliah; Istanto (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the role of the principal's leadership style in enhancing the competitiveness of Madrasah Tsanawiyah Nahdlatul Muslimat (MTs NDM) Surakarta. The leadership style applied by each school principal is different. The research subject is the principal of MTs NDM Surakarta. MTs NDM, which also functions as an Islamic boarding school, offers a unique appeal compared to other madrasahs, as it requires students to reside in dormitories. The leadership style adopted by the principal is collegial-collective, which contributes to the continuous progress of the school. Key strategies implemented include optimizing facility and infrastructure management, improving the quality of educational processes through innovation by adopting strengths from other institutions, enhancing teacher competencies through webinars, integrating general, religious, and tahfidz subjects, and engaging parents and the community. This research employs a qualitative descriptive method to examine the principal's efforts in increasing the school's competitiveness. Data were collected through interviews and direct observations to obtain a comprehensive and systematic understanding of the leadership approach, strategies employed, and challenges faced.